2020
DOI: 10.3390/pathogens9070531
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Seedborne Fungi and Pathogenicity of Fusarium Species Associated with Intercropped Soybean

Abstract: Maize/soybean relay strip intercropping has been widely practiced in Southwest China due to its high productivity and effective application of agricultural resources; however, several seedborne diseases such as seedling blight, pod and seed decay are frequently observed causing severe yield loss and low seed quality. So far, the population and pathogenicity of the seedborne fungi associated with intercropped soybean remain unexplored. In this study, seeds of 12 soybean cultivars screened for intercropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 50 publications
1
25
0
2
Order By: Relevance
“…In addition, F. meridionale was also recently reported as pathogen in root rot on soybean under monoculture and ear rot on maize 42,43 . Moreover, F. asiaticum has been reported as a major and dominant causal agent of FHB on wheat and barley in China [44][45][46] and was also detected as a pathogen causing Gibberella ear rot of maize and seedborne diseases of soybean 47,48 . Although F. meridonale and F. asiaticum were not predominant species in the present study, with low isolation frequencies, they were reported in China for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, F. meridionale was also recently reported as pathogen in root rot on soybean under monoculture and ear rot on maize 42,43 . Moreover, F. asiaticum has been reported as a major and dominant causal agent of FHB on wheat and barley in China [44][45][46] and was also detected as a pathogen causing Gibberella ear rot of maize and seedborne diseases of soybean 47,48 . Although F. meridonale and F. asiaticum were not predominant species in the present study, with low isolation frequencies, they were reported in China for the first time.…”
Section: Discussionmentioning
confidence: 99%
“… Zeng et al (2019) indicated that the rhizosphere interactions in a mixture model are helpful in recruiting beneficial microbes, which are closely related to the improvement of plant quality in contaminated soil. Additionally, other typical systems of crop production, such as maize-peanut intercropping ( Li et al, 2018 ), maize-soybean intercropping ( Chang et al, 2020 ), and millet-sorghum intercropping ( Iijima et al, 2016 ), have provided evidence of change of microbial communities and enhancement of biotic or abiotic stress tolerance. Thus, the recruitment of specific microbial communities under particular production conditions is an interesting topic.…”
Section: Introductionmentioning
confidence: 99%
“…This association between seeds and pathogens is an important means for the pathogens to spread on a large scale and a way to guarantee their survival in nature [ 7 , 8 , 9 ]. Seedborne pathogens can limit the production of many crops and can result in severe economic losses to growers [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%